Performance and exhaust emissions rate of small-scale turbojet engine running on dual biodiesel blends using Gasturb - Mohammed Altarazi, Yazan Sofyan; Abu Talib, Abd Rahim; Gires, Ezanee; Yu, Jianglong; Lucas, John; Yusaf, Talal (Elsevier, 2021)
Gas turbines are designed to run on specific fuels such as conventional fuels, so researchers are working to find alternative fuels as biodiesel. The purpose of this study is predicting the engine performance and emissions rate for the KingTech K180 turbojet engine running on dual biodiesel and its blend with Jet-A fuel. Besides that, this paper explores the different effect between dual blends and single blend. The fuel parameters were calculated based on each fuel's physicochemical properties to produce nine different blends of dual biodiesel (B10-Jet, B30-Jet, B50-Jet, B70-Jet, and B90-Jet) and a single biodiesel blend (POME50: Jet-A50). Then the heat of combustion for each blend was obtained using the GasTurb Details-6. After that, the design point was determined of the specific engine and operates it using alternative fuels to analyze the performance and emissions characteristics (CO, CO2, and NOx). This study found that the B10-Jet blend gave the best specific fuel consumption (SFC) value, 42.43 (g/kN.s). It also produced a lower emissions rate for CO and CO2 than Jet-A fuel and other blends. While emission index NOx was high for all blends, except B10-Jet fuel value was close to Jet-A fuel emission value.